Iron-Rich Foods Intakes among Urban Senegalese Adolescent Girls - Ndiaye, Aminata Ndene; Galibois, Isabelle; Blaney, Sonia (International Journal of Child Health and Nutrition, 2021)
Intake of iron-rich foods was investigated in Senegalese adolescent girls. A cross-sectional survey was conducted among 136 girls aged 13 to 18, attending two colleges in Dakar. Data on the consumption of iron-rich foods over the previous week were collected through a food frequency questionnaire. Results show that 12% of the girls had consumed dishes made with iron-rich foods 3 times or less in the past seven days, 34%, 4 to 6 times, and 54%, 7 times and above. However, 83% of the girls had anntake of iron-rich foods below the 84 g per day recommended for animal protein sources by the EAT-Lancet Commission on Healthy Diets from Sustainable Food Systems. The diet of Senegalese adolescent girls seems conducive to iron deficiency. To define effective interventions to improve the situation, investigating underlying factors to the low consumption of iron-rich foods is warranted.